Análisis de evolución de la confianza en la industria de automóvil: Hemos llegado a la confianza identificativa? - I. Martín Rubio; C. Peligros Espada (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
The aim of this paper is to study the evolution of the trust in the relationships between carmakers and their suppliers. The importance of the trust for the good performance of the relation has been recognized in the economic literature, but now is considerated a vital aspect. We use the Lewicki and Bunker model, because it has been extensively utilized in the literature and it fits in a quite good way to our purposes. We conclude that the car industry is situated in the phase of the Knowledge Based Trust, and it hasn't achieve the phase of Identification Based Trust.
Keywords: 330; trust; automotive industry; Lewicki-Bunker model